Agindo nas brechas dos “Podres poderes”: caminhadas, coletivos e movimentos pela cidade - Pinto, Igor Moreira de Sousa (2023)
The thesis that follows is based on social anthropological research on politics, understood as collective actions, the constitution of arenas and the generation of events through collective arrangements that impact and affect social reality and power relations. Research developed over a long period of experiences with people and collectives who act from peripheries territories, on the margins of centers of institutional power, in confrontation with logics, practices and strategies such as segregation, removal, extermination. Subjects who fight, acting in the gaps of “rotten powers” (state, market and criminal) to resist, create, transform and produce life, and who, to this end, connect and implement shared practices and strategies in their resistance. In the research, I mobilize practices and strategies from the Anthropology of Politics to grasp, understand and explain the being-doing-thinking movement in the popular field of the city of Fortaleza-Ce, with its territories, collectives and people, their worldviews, moral dispositions, organizational cultures and motivations to act. Their walks, in which those who walk feel, think and act, transforming the reality around them and transforming themselves into movement, which crosses and transcends individuals and their trajectories. Community, Occupation, Popular Assembly, Poetry slam, are some of the categories, engendered in the flows of collective action in the time-space of the research, which cross the text of the thesis, as well as arrangements of memory, territories, displacements and encounters. Through narratives, we cover events, conflicts, actions and creations that have led to struggles in the last two decades in Fortaleza, Ceará, in connection with similar problems and struggles in other cities, around issues such as the right to the city, human rights, combating social inequalities, recognition, freedom, common good... To this end, the thesis is divided into five intertwined parts: Occupy, resist and produce life; popular assemblies and struggles for existence; The party and art as political action; Popular Assemblies for the Right to the City and Poetry slam; Other itineraries: notes on overflows.